Impact of gender on efficacy and acute toxicity of alkylating agent -based chemotherapy in Ewing sarcoma: Secondary analysis of the Euro-Ewing99-R1 trial. Issue 16 (November 2015) - van den Berg, Henk; Paulussen, Michael; Le Teuff, Gwénaël; Judson, Ian; Gelderblom, Hans; Dirksen, Uta; Brennan, Bernadette; Whelan, Jeremy; Ladenstein, Ruth Lydia; Marec-Berard, Perrine; Kruseova, Jarmila; Hjorth, Lars; et al.
Abstract Background Based on the randomised Euro-EWING99-R1 trial, vincristine, adriamycin, cyclophosphamide (VAC) may be able to replace vincristine, adriamycin, ifosfamide (VAI) in the treatment of standard-risk Ewing sarcoma. However some heterogeneity of treatment effect by gender was observed. The current exploratory study aimed at investigating the influence of gender on treatment efficacy and acute toxicity. Patients and methods Impact of gender on event-free survival (EFS), acute toxicity by course, switches between treatment arms and cumulative dose of alkylating agents was evaluated in multivariable models adjusted for age including terms to test for heterogeneity of treatment effect by gender. The analysis of the EFS was performed on the intention-to-treat population. Results EFS did not significantly differ between the 509 males and 347 females (p = 0.33), but an interaction in terms of efficacy was suspected between treatment and gender (p = 0.058): VAC was associated with poorer EFS than VAI in males, hazard ratio (HR) (VAC/VAI) = 1.37 [95% confidence interval (CI), 0.98–1.90], contrasting with HR = 0.81 [95%CI, 0.53–1.24] in females. Severe toxicity was more frequent in females, whatever the toxicity type. Thirty patients switched from VAI to VAC (9/251 males, 4%, and 21/174 females, 12%) mostly due to renal toxicity, and three from VAC to VAI (2/258 males, 0.8%, and 1/173 females, 0.6%). A reduction of alkylating agent cumulative dose >20% was more frequent in females (15% versus 9%, p = 0.005), with no major difference between VAC and VAI (10% versus 13%, p = 0.15). Conclusion Differences of acute toxicity rate and cumulative doses of alkylating agents could not explain the marginal interaction observed in the Euro-EWING99-R1 trial data. Effects of gender-dependent polymorphism/activity of metabolic enzymes (e.g. known for CYP2B6) of ifosfamide versus cyclophosphamide should be explored. External data are required to further evaluate whether there is heterogeneity of alkylating agent effect by gender. Trial numbers NCT00987636 and EudraCT 2008-003658-13.